Educational Management and Psychological Resilience: Effects of Role Conflict, Stress, Burnout on Job Satisfaction in Military Education Institutions - Mustika Dwi Dinarsih; Hardani Widhiastuti; Rusmalia Dewi (Journal of Educational Management Research, 2026)
This study aims to examine the effects of role conflict and job stress on job satisfaction through burnout, while highlighting the role of psychological resilience within educational management contexts. A qualitative approach with a phenomenological design was employed to explore individuals’ lived experiences in managing organizational demands. Data were collected through in-depth, semi-structured interviews with purposively selected participants who had experienced workplace conflict and job-related stress. The data were analyzed using thematic analysis, including data condensation, display, and verification. The findings reveal that role conflict and job stress contribute to emotional exhaustion, decreased motivation, and negative work perceptions. Burnout emerges as a key mediating mechanism linking job demands to job satisfaction. However, individuals who demonstrate adaptive coping strategies—such as problem-focused coping, emotional regulation, and meaning-making—show higher psychological resilience and better job satisfaction. From an educational management perspective, leadership practices, communication systems, and institutional support significantly influence these psychological dynamics. This study implies that strengthening educational management strategies, including psychological support systems and stress management programs, is essential to enhance job satisfaction and sustain organizational effectiveness.